2022
DOI: 10.14715/cmb/2021.67.6.21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Detection of Human Papilloma Virus DNA and E6/E7 mRNA for Cervical Cancer Patients

Abstract: This study aimed to explore the clinical significance of detection of human papillomavirus (HPV) DNA and E6/E7 mRNA for cervical cancer patients. For this purpose, a total of 300 patients with cervical lesions who performed the colposcopy examination for the cervix between January 2018 and January 2020 were divided into three groups according to the level of cervical intraepithelial neoplasia (CIN): Low-level group (Group A, n = 101), high-level group (Group B, n = 149), cervical cancer group (Group C, n = 50)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…For instance, Valença et al, reported in their study that out of 111 women who underwent biopsy and an E6/E7 test, the positivity rate of the E6/E7 test was 84.7% in women with cervical intraepithelial neoplasia (CIN) grade 2 or higher lesions [26]. In addition, Yu and Wang 2022 reported that the presence of HPV DNA and HPV E6/E7 mRNA were significantly higher in cases of CIN and cervical cancer than in cases of inflammation of the cervix [32]. Yu and Wang also reported that the specificity of HPV E6/E7 mRNA was lower than that of HPV DNA in detecting low-grade intraepithelial neoplasia, but it performed better in detecting high-grade intraepithelial neoplasia and cervical cancer [32].…”
Section: Hr-hpv Frequency (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Valença et al, reported in their study that out of 111 women who underwent biopsy and an E6/E7 test, the positivity rate of the E6/E7 test was 84.7% in women with cervical intraepithelial neoplasia (CIN) grade 2 or higher lesions [26]. In addition, Yu and Wang 2022 reported that the presence of HPV DNA and HPV E6/E7 mRNA were significantly higher in cases of CIN and cervical cancer than in cases of inflammation of the cervix [32]. Yu and Wang also reported that the specificity of HPV E6/E7 mRNA was lower than that of HPV DNA in detecting low-grade intraepithelial neoplasia, but it performed better in detecting high-grade intraepithelial neoplasia and cervical cancer [32].…”
Section: Hr-hpv Frequency (%)mentioning
confidence: 99%
“…In addition, Yu and Wang 2022 reported that the presence of HPV DNA and HPV E6/E7 mRNA were significantly higher in cases of CIN and cervical cancer than in cases of inflammation of the cervix [32]. Yu and Wang also reported that the specificity of HPV E6/E7 mRNA was lower than that of HPV DNA in detecting low-grade intraepithelial neoplasia, but it performed better in detecting high-grade intraepithelial neoplasia and cervical cancer [32]. Furthermore, Cao et al reported that the total E6/E7 mRNA positivity rate was 67.27%…”
Section: Hr-hpv Frequency (%)mentioning
confidence: 99%
“…Despite being a deadly disease, CC can be cured if it can be detected in the early stages [12,13]. For clinical initiative, it is a very crucial task to identify the cancerous cell which is known as a cyst [14]. Detecting cyst from cervix images ensures clinicians for patients regarding CC.…”
Section: Introductionmentioning
confidence: 99%